2012
DOI: 10.1016/j.ijgo.2012.05.033
|View full text |Cite
|
Sign up to set email alerts
|

The effect of post‐cesarean rectal misoprostol on intestinal motility

Abstract: After cesarean delivery, rectal misoprostol had the added benefit of inducing intestinal motility. Misoprostol might be considered in a clinical setting where postoperative ileus is anticipated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…17,22,23,63 Some trials have reported that misoprostol has the additional effect of increasing intestinal motility after cesarean delivery and allowing early oral feeding, which could reduce the risk of postoperative ileus and shortened hospital stay length, and allow early breastfeeding. 64-66 This effect has been reported in trials that administered misoprostol rectally after surgery, but it is unclear if similar effects can be obtained if the drug is administered sublingually.…”
Section: Commentmentioning
confidence: 83%
“…17,22,23,63 Some trials have reported that misoprostol has the additional effect of increasing intestinal motility after cesarean delivery and allowing early oral feeding, which could reduce the risk of postoperative ileus and shortened hospital stay length, and allow early breastfeeding. 64-66 This effect has been reported in trials that administered misoprostol rectally after surgery, but it is unclear if similar effects can be obtained if the drug is administered sublingually.…”
Section: Commentmentioning
confidence: 83%
“…The aetiology and pathogenesis of POI is multifactorial; therefore, a multimodal approach is required to counteract the morbidity of POI. These measures include preoperative optimisation; gentle bowel handling; early feeding; avoidance of nonessential use of nasogastric tubes; thoracic epidural analgesia; use of pharmacological agents such as water‐soluble contrast agents, alvimopan (a selective μ ‐receptor opioid antagonist), misoprostol and ketorolac; and gum chewing …”
Section: Introductionmentioning
confidence: 99%
“…Intraoperative blood loss was routinely calculated in all the patients using the formula: (A + B) -C 20 , in which A refers to the difference between pre-and post-surgery weights of surgical towels in grams were determined with the precision digital scales, B refers to the volume of the contents of the "suction" bottle (ml), and C refers to the amniotic fluid volume (AFV) (ml).The uterus was divided into four quadrants, by the linea nigra, to the right and left quadrants, and the umbilicus to the lower and upper quadrants. The deepest vertical diameter of the amniotic fluid was measured in centimeters per quadrant 21 .…”
Section: Methodsmentioning
confidence: 99%
“…When the literature is reviewed, although there are many publications with the use of rectal misoprostol and postpartum bleeding, only two studies on intestinal motility have been identified. The role of rectal misoprostol administration on intestinal motility was effective in one of these studies and ineffective in the other 17,20 . To contribute to the uncertainty in this matter this study was designed to determine the effectiveness of rectal administered misoprostol in inducing the early motility of the gastrointestinal tract and reducing the amount of postpartum uterine bleeding in primiparous women.…”
Section: Introductionmentioning
confidence: 97%